2017
DOI: 10.25134/jrka.v3i1.676
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Kepemilikan Institusional Dan Kepemilikan Manajerial Terhadap Manajemen Laba

Abstract: This study aims to analyze the effect of profitability, leverage, firm size, institutional ownership and managerial ownership of earnings management. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange from 2010 to 2015. The sample in this study as many as 47 companies for 6 years.The result of analysis shows that profitability have a significant positive effect to earnings management, firm size and managerial ownership negatively affect earnings management, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
42
2
126

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(182 citation statements)
references
References 1 publication
12
42
2
126
Order By: Relevance
“…Those results indicate the higher the size of the company's then management will increasingly profit decline. The results of this research consistent with [15] which concluded that the size of the company's influential negatively to earnings management, which means that the larger the size of the company, then the smaller the management of earnings management is done in the his company.…”
Section: ) Influence Of the Size Of The Company Towards The Managemesupporting
confidence: 85%
“…Those results indicate the higher the size of the company's then management will increasingly profit decline. The results of this research consistent with [15] which concluded that the size of the company's influential negatively to earnings management, which means that the larger the size of the company, then the smaller the management of earnings management is done in the his company.…”
Section: ) Influence Of the Size Of The Company Towards The Managemesupporting
confidence: 85%
“…The higher the leverage, the greater the company's debt, so the greater the risk faced by company management. As a result, these conditions encourage company management to perform income smoothing in line with the results of [14] in [15]. Likewise, research conducted by [16] states that high leverage encourages company management to manage earnings.…”
Section: Introductionsupporting
confidence: 63%
“…Profitability is the company's ability to earn profits through all of its resources and capabilities (Purnama, 2017). Profitability has important information for external parties because if the profitability is high, it can be determined that the company's performance is good.…”
Section: Introductionmentioning
confidence: 99%